Pivoting in the Time of COVID-19: An in-Depth Case Study at the Nexus of Food Insecurity, Resilience, System Re-Organizing, and Caring for the Community - Fox, Rebekah; Frye, Joshua (Frontiers in Communication, 2021)
According to the School Nutrition Association, nearly 100,000 schools serve free or reduced school lunches and breakfasts daily to approximately 34.34 million students nationwide. However, as COVID-19 forced many schools to close, students who depended on the public schools to meet the majority of their nutritional needs faced an even larger battle with food insecurity. In light of this, the USDA Food and Nutrition Service (FNS) introduced “key flexibilities” and contingencies to existing programs such as the Supplemental Nutrition Assistance Program (SNAP), Child Nutrition Programs, Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), among others. For example, the Nationwide Parent/Guardian Meal Pick-up Waiver allowed parents/guardians to pick-up meals and bring them home to their children though the 2020-2021 school year. Even with all of this flexibility being introduced into the system, unmet need continued to be a problem in many communities. A survey of school nutrition professionals conducted from April 30th-May 8th representing 1,894 school districts nationwide, showed that “95% of respondents were engaged in emergency meal assistance, and combined, these districts reported serving more than 134 million meals in April alone.” Recognizing this unmet need, and that food insecurity was intertwined with other needs within the community, the Crystal Bridges Museum of American Art and its satellite contemporary art space the Momentary, partnered with the Northwest Arkansas Food Bank and over 30 additional partner organizations to pivot their existing outreach services. This case study illuminates how communication processes can support adaptive crisis behavior, organizational restructuring, building resilience, and creatively advancing food security . Specifically, we seek to identify lessons learned by Crystal Bridges during the pivoting process, that might be useful for other organizations who seek to foster meaningful engagement with the public, especially in times of crisis. To this end, we performed a textual analysis of the in-depth evaluation materials produced by Crystal Bridges (based on data gathered before, during, and after the pivot) to identify barriers and facilitators to reaching their goals.